2021
DOI: 10.1213/ane.0000000000005639
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Is an Early Plasma Marker of Severe Postoperative Complications in Thoracic Surgery: Exploratory Results From a Substudy of a Randomized Controlled Multicenter Trial

Abstract: BACKGROUND: Postoperative complications in surgery are a significant burden, not only for the patients but also economically. While several predicting factors have already been identified, it is still not well known if increased levels of inflammatory markers in the immediate perioperative phase correlate with a higher incidence of postoperative complications. This study aimed to evaluate which patient characteristics and intraoperative parameters correlate with increased plasma values of monocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“… 19 , 20 CRP is associated with an increased risk for POD 35 and IL-6 has a clear association with severe postoperative complications in thoracic surgery. 36 In our study, we found that, compared to NS, dexmedetomidine reduced CRP and IL-6 postoperatively. This finding may provide evidence for the anti-inflammatory effects of dexmedetomidine.…”
Section: Discussionsupporting
confidence: 48%
“… 19 , 20 CRP is associated with an increased risk for POD 35 and IL-6 has a clear association with severe postoperative complications in thoracic surgery. 36 In our study, we found that, compared to NS, dexmedetomidine reduced CRP and IL-6 postoperatively. This finding may provide evidence for the anti-inflammatory effects of dexmedetomidine.…”
Section: Discussionsupporting
confidence: 48%
“…Clinical trials have shown that minimally invasive videoassisted thoracoscopic surgery (VATS) attenuates the inflammatory response and maintains immune cell function compared to open thoracotomy. In studies that compared VATS and thoracotomy in patients undergoing lobectomy, lower serum IL-6 and CRP levels were reported in patients who underwent VATS (84)(85)(86). A study that evaluated IL-6 levels in the pleural fluid following lobectomy also demonstrated that the increase in pleural IL-6 levels 3 h after surgery was significantly lower after VATS compared to open lobectomy (87).…”
Section: Extent Of Tissue Injurymentioning
confidence: 99%